Geração de cenários de teste com base em casos de uso - Octaviano, Fábio Roberto (2011)
Around 37% of unsuccessfully software projects have their cause related to issues on how to software requirements are collected and manipulated. Requirement Management activities help on getting this scenario better, however it is necessary to validate the software under construction on its right meaning frequently. Thus, Software Quality Assurance (SQA) activities are very important to find defects on softwares under development, even before having an executable product version. The main SQA activities are Test and Inspection and, in spite of Test activity generally occurs during coding phase, this activity may and should be applied as soon as possible, as it needs planning to achieve its goal. Besides, many important Test Cases and Scenarios are specified once software development starts, during requirement specification and modeling phases. Thus, considering this scenario and also that Use Case Model is one of the most used techniques of requirement modeling, this work has the objective of implementing a module to generate Test Scenarios based on Use Cases. The module is a new added functionality to COCAR environment, which supports other software development activities based on use case model. This new module helps on Test activity automation, generating unity testing scenarios, related to each use case, and integration testing scenarios, that use the relationships among use cases, based on their specifications. The work evaluation was done based on real developed software, comparing the used test cases with the test scenarios generated by COCAR environment. The results have shown that the generated test scenarios have almost all of the used test cases matching. Thus, they can be used to support test plan and test cases definition.